Studi Korelasi Pengetahuan Sains dan Sikap Terhadap Sains di SMA Santo Paulus Pontianak - Suliono Suliono; Afandi Afandi; Indri Astuti (University of Bengkulu, 2022)
Indonesian education currently focuses on improving 21st-century skills, one of which is scientific literacy. This study aims to provide information related to the profile of general science knowledge and attitudes towards science and the relationship between scientific knowledge and attitudes towards science. This research was a quantitative descriptive study using the High School General Science Knowledge Survey and Modified Attitudes toward Science Inventory instrument. The correlation of the two variables has been tested by the Pearson Product moment test using SPSS with a significance level of 5%. The results showed that the student's general science knowledge achievement was in the medium category with an average score of 44.06. Students have the lowest achievement in the aspect of designing and evaluating scientific investigations and the highest in the aspect of explaining scientific phenomena. Attitudes towards science on the indicators of perception of the teacher and the value of science to society showed positive approval in the high category, while attitudes toward the indicators of anxiety towards science, confidence in science, and the desire to do science were in the medium category. The results of the correlation test found the value of sig. (2-tailed) 0.114 > 0.05. Thus, it was concluded that there was no significant effect between attitudes towards science and knowledge of science.